1982
DOI: 10.1007/bf02123317
|View full text |Cite
|
Sign up to set email alerts
|

Release of endotoxic lipopolysaccharide by sensitive strains ofEscherichia coli submitted to the bactericidal action of human serum

Abstract: Free endotoxin was assayed in filtered samples of E. coli suspensions submitted to the bactericidal and bacteriolytic action of 10% human serum. The Limulus amoebocyte lysate test, a passive hemolysis inhibition assay based on O antigenic specificity and the determination of 3-OH-myristic acid by mass spectrometry were used as assay methods differing from one another with regard to the part of the endotoxin macromolecule involved in the reaction. The biological activity of endotoxin was assessed in a mouse let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Airborne endotoxins may exist in a bound or free state (Demonty and Grawe, 1982). Bound endotoxins remain bound to the bacterial outer membrane, whereas free endotoxins are shed from membrane complexes containing phospholipids, proteins, and LPS.…”
Section: Airborne Endotoxin Analysismentioning
confidence: 99%
“…Airborne endotoxins may exist in a bound or free state (Demonty and Grawe, 1982). Bound endotoxins remain bound to the bacterial outer membrane, whereas free endotoxins are shed from membrane complexes containing phospholipids, proteins, and LPS.…”
Section: Airborne Endotoxin Analysismentioning
confidence: 99%
“…The endotoxin may exist bound to the bacterial outer membrane or as shed membrane complexes containing phospholipid, protein, and LPS (9, 29). Since bacteria often are found in low numbers in blood and experimental studies have shown that bacteria are rapidly cleared from the circulation by the reticuloendothelial system, a major contribution to the induced symptoms may come from endotoxin shed by the bacteria or released by lysis (9,32,36). Such smaller membrane fragments may penetrate to areas of tissues which could be poorly reached by bacteria.…”
mentioning
confidence: 99%
“…First, a common observation in previous studies is the dissociation between lethality and an increase in the endotoxin concentration; that is, the period of maximal increase in endotoxin followed the period of cell death by 1 h (3) and by up to 3 h (13). This contrasts with the release of lipopolysaccharide from serum-affected bacteria, which as 51Cr-labeled lipopolysaccharide is 80% complete within 7 min (10) and 99% complete within 15 min (37) of cell death and as activity in the LAL assay is more than 90% complete within 12 min of cell death, although neither cell death nor lipopolysaccharide release is seen with heat-inactivated serum (8). The findings in this study support this dissociation between lethality and the maximal increase in endotoxin concentration after antibiotic exposure.…”
Section: Discussionmentioning
confidence: 87%